Synthesis and characterization of Ni(II), Cu(II), Zn(II) and Cd(II) complexes of a new vic-dioxime ligand - Canpolat, E; Kaya, M (Taylor & Francis Ltd, 2002)
In this study, 1,2-dihydroxyimino-3,7-di-aza-9,10-O-alpha-methyI benzal decane (LH2) was synthesized starting from 1,2-O-alpha-methyl benzal-4-aza-7-amino heptane (RNH2) and antichloroglyoxime. With this ligand, complexes were synthesized using Ni(II) and Cu(II) salts with a metal: ligand ratio of 1: 2. However, the reaction of the ligand with salts of Zn(II) and Cd(II) gave products with metal: ligand ratio of 1 : 1. Structures of the ligand and its complexes are proposed based on elemental analyses, IR, C-13- and H-1-NMR spectra, magnetic susceptibility measurements and thermogravimetric analyses (TGA).
Keywords: vic-dioxime; transition metal complexes; nickel(II); copper(II); zinc(II); cadmium(II)